Metabolic decline in an insect ear: correlative or causative for age-related auditory decline? - Austin, Thomas T.; Thomas, Christian L.; Lewis, Clifton; Blockley, Alix; Warren, Ben (Frontiers in Cell and Developmental Biology, 2023)
One leading hypothesis for why we lose our hearing as we age is a decrease in ear metabolism. However, direct measurements of metabolism across a lifespan in any auditory system are lacking. Even if metabolism does decrease with age, a question remains: is a metabolic decrease a cause of age-related auditory decline or simply correlative? We use an insect, the desert locust Schistocerca gregaria, as a physiologically versatile model to understand how cellular metabolism correlates with age and impacts on age-related auditory decline. We found that auditory organ metabolism decreases with age as measured fluorometrically. Next, we measured the individual auditory organ’s metabolic rate and its sound-evoked nerve activity and found no correlation. We found no age-related change in auditory nerve activity, using hook electrode recordings, and in the electrophysiological properties of auditory neurons, using patch-clamp electrophysiology, but transduction channel activity decreased. To further test for a causative role of the metabolic rate in auditory decline, we manipulated metabolism of the auditory organ through diet and cold-rearing but found no difference in sound-evoked nerve activity. We found that although metabolism correlates with age-related auditory decline, it is not causative. Finally, we performed RNA-Seq on the auditory organs of young and old locusts, and whilst we found enrichment for Gene Ontology terms associated with metabolism, we also found enrichment for a number of additional aging GO terms. We hypothesize that age-related hearing loss is dominated by accumulative damage in multiple cell types and multiple processes which outweighs its metabolic decline.